Possibilities and challenges of using the internet and digital tools in 5th grade classes at municipal schools in Colméia (Research, Society and Development, 2022)
The basis of the formation of individuals is the school. In this context, for some time now, the internet has been taking up space within classrooms, so its use is increasingly present and necessary in this environment, allowing a new look at education and raising some questions about the benefits and harms of this introduction. . The study of this research has as its theme the possibilities and challenges of using the internet and digital tools within the classroom, and aims to understand the importance of using the internet/digital tools for the student’s teaching-learning process. Having as problematic what is the teaching vision through the use of the internet inside the classroom? Thus, the methodology applied was field research of a qualitative nature, as it allows direct contact between the researcher and the object of study. Through this analysis, it was possible to identify the biggest difficulties faced by educators and what benefits the use of digital tools can bring to the student, and understand that they help students to develop their digital skills in a practical way, in order to be carried out in the classroom. Everyday life, whether inside or outside the classroom. In conclusion, it is up to the teacher to rethink methodologies and analyze how the internet is being used in the classroom, as it is feasible for the educator to insert educational applications or even social networks in the pedagogical practice.